Analysis of financial literacy and its determinants: a study among university students in UTAR Kampar - Chan, Hao Chuan; Chong, Ka Chun; Heng, Boon Seng; Teh, Ke-Vin; Tey, Zhin Yong (2022)
This study investigates and analyzes the determinants of financial literacy among the university students in UTAR Kampar. The explanatory variables, which is the determinants consists of financial education, money attitude (power-prestige), money attitude (retention-time), money attitude (distrust), and money attitude (anxiety). In this study, primary data is the only method and 418 respondents have filled-up the questionnaire even the requirement of the sample size is 379 respondents. All of the respondents are UTAR Kampar students and IBM SPSS Statistics 28 was used to generating the data for the analyze and interpretation. Besides, this study was explored using descriptive analyses, pilot test, reliability analyses, normality test, Multiple Regression Analysis, and Pearson’s Correlation Coefficient. In this study, it found out that MAPP, MART, MAD are statistically significant impact on the financial literacy. However, financial education, MAA and gender are not statistically significant impact. On the other hand, it mentioned the implications, limitations, and recommendation of the study to provide some assistances for the future research regarding to this topic.